1982
DOI: 10.1002/net.3230120406
|View full text |Cite
|
Sign up to set email alerts
|

An efficient algorithm for K shortest simple paths

Abstract: This article gives an efficient algorithm for obtaining K shortest simple paths between two specified nodes in an undirected graph G with non-negative edge lengths. Letting n be the number of nodes and m be the number of edges in G, its running time is

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
132
0
6

Year Published

1999
1999
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 225 publications
(138 citation statements)
references
References 22 publications
0
132
0
6
Order By: Relevance
“…, K}, and the new paths are candidates to a future p j , with j > k, therefore they are stored in X. The paths to be generated from each p k are the quickest in a partition of path sets proposed by Katoh et al [4].…”
Section: A Review Of the K-quickest Path Algorithmmentioning
confidence: 99%
“…, K}, and the new paths are candidates to a future p j , with j > k, therefore they are stored in X. The paths to be generated from each p k are the quickest in a partition of path sets proposed by Katoh et al [4].…”
Section: A Review Of the K-quickest Path Algorithmmentioning
confidence: 99%
“…On the one hand we have adaptations of K shortest loopless path algorithms, while on the other hand we can consider a generalisation of the methods used to solve the quickest path problem. In the first group we describe the approaches by Rosen, Sun, and Xue (1991), which is an adaptation of the algorithm by Yen (1971), and Pascoal, Captivo, and Clímaco (2005), who, in turn, adapted the algorithm by Katoh, Ibaraki, and Mine (1982). In the second we review the algorithm by Chen (1994).…”
Section: Ranking K Quickest Loopless Pathsmentioning
confidence: 99%
“…, K . The difference between the two algorithms is the partition used to generate new candidates to store in X , as presented by Katoh, Ibaraki, and Mine (1982). Let p j be the parent of some loopless path p k and:…”
Section: B R ) ← Arc Bandwidth Values By Increasing Ordermentioning
confidence: 99%
See 1 more Smart Citation
“…In the ÿrst class, Yen [13] proposed a very e cient algorithm that ÿnds the ÿrst K simple paths in a general network in O(K|V | 3 ) time, where |V | is the number of nodes. Katoh et al [14] improved the time bound to be O(K(|A| + |V | log|V |)) for an undirected network, where |A| is the number of arcs. Recently, Hadjiconstantinou and Christoÿdes [15] presented an e cient implementation of a KSP algorithm based on the method of Katoh et al [14]; they suggested that the KSP algorithm is suitable for ÿnding a large number of simple paths between any pair of nodes.…”
Section: Introductionmentioning
confidence: 99%